Contemporary views on multiple application of self-etch adhesives – review of literature - Żęcin-Dereń, Anna; Sokołowski, Jerzy; Łapińska, Barbara (Journal of Stomatology, 2015)
Introduction. Introducing one-step self-etch adhesives (all-in-one) to adhesive dentistry was intended to simplify clinical procedures and increase the bond strength between the composite material and dentine when compared to self-etch two-step or etch-and-rinse adhesives. These requirements failed to be fulfilled. All-in-one adhesives create an inadequate bond strength with dentine; hence they are blamed for the lack of marginal integrity, marginal discoloration and poor retention of fillings. Many authors suggest the change in the application of all-in-one adhesives in order to improve their properties. Aim of the study. To summarize the results of available contemporary research on the influence of the multiple application of all-in-one self-etch adhesives on the bond strength between resin and dentine. Conclusions. Given the results of scientific papers as well as differences in the chemical composition of various self-etch all-in- one adhesives, their individual application should be determined. Based on the majority of reviewed laboratory studies, an application of two or three layers of the adhesive may increase the bond strength of one-step self-etch adhesives to dentine.